Stochastic volatility : selected readings - Shephard, Neil. (Oxford ; New York : Oxford University Press, 2005)
This book brings together some of the main papers that have influenced this exciting new field, and shows that the development of this subject has been highly multidisciplinary, and has helped to produce methods and models for the realistic pricing of options, efficient asset allocation, and accuraterisk assessment. A lengthy introduction by the editor, a leader in the field, connects the papers with the literature.
Includes bibliographical references and indexes.
nmn 24/04/13
Loans
Keywords: Econometrics; Stochastic processes; Finance; Money market; Capital market